The Influence of Corporate Social Responsibility, Green Accounting, Intellectual Capital, and Firm Size on Financial Performance with Good Corporate Governance as a Moderating Variable : An Empirical Study of Mining Companies Listed on the Indonesia Stock Exchange, 2020–2024 - Ahmad Aulia Dalimunthe; Erlina Erlina; Idhar Yahya (International Journal of Economics, Management and Accounting, 2026)
This study aims to determine and analyze the effect of Corporate Social Responsibility, Green Accounting, Intellectual Capital, and Firm Size on Financial Performance with Good Corporate Governance as a moderating variable. This study was conducted on mining companies listed on the Indonesia Stock Exchange (IDX) for a five-year period, namely 2020–2024. The study population consisted of 34 mining companies, with the sampling method using purposive sampling, resulting in 33 companies as research samples. The information used was derived from secondary sources, namely annual reports and sustainability reports. Multiple linear regression and Moderated Regression Analysis (MRA) were used to analyze the data, with the assistance of EViews software. The results showed that Corporate Social Responsibility had a positive and significant effect on Financial Performance. Green Accounting and Intellectual Capital also had a positive and significant effect on Corporate Social Responsibility. Meanwhile, Firm Size had a positive but insignificant effect on Financial Performance. The results of the moderation test indicate that Good Corporate Governance is unable to moderate the influence of CSR, Green Accounting, Intellectual Capital, or Firm Size on Financial Performance. This finding suggests that increasing social responsibility, implementing green accounting, and managing intellectual capital can improve the financial performance of mining companies, but their effectiveness has not been strengthened by corporate governance mechanisms.